GIS based frequency ratio method for landslide susceptibility mapping at Da Lat City, Lam Dong province, Vietnam - Thanh, Dang Quang; Nguyen, Duy Huu; Prakash, Indra; Jaafari, Abolfazl; Nguyen, Viet -Tien; Phong, Tran Van; Pham, Binh Thai (Vietnam Journal of Earth Sciences, 2020)
Landslide susceptibility mapping of the city of Da Lat, which is located in the landslide prone area of Lam Dong province of Central Vietnam region, was carried out using GIS based frequency ratio (FR) method. There are number of methods available but FR method is simple and widely used method for landslide susceptibility mapping. In the present study, eight topographical and geo-environmental landslide-conditioning factors were used including slope, elevation, land use, weathering crust, soil, lithology, distance to geology features, and stream density in conjunction with 70 past landslide locations. The results show that 6.27% of the area is in the very low susceptibility area, 21.03% in the low susceptibility area, 27.09% in the moderate susceptibility area and 27.41% of the area is in the high susceptibility zone and 18.21% in the very high susceptibility zone. The landslide susceptibility map produced in this study helps to assist decision makers in proper land use management and planning.